Mast Cells Association in Different Grades Dysplasia & Oral Squamous Cell Carcinoma: A Histochemical Study (International Journal of Food and Nutritional Sciences, 2022)
Introduction : Angiogenesis is a complex process mediated by angiogenic factors which get produced by cancer cells mast cells play a key role in promoting angiogenesis thus they are related with progression of tumor and metastasis. Tryptase found as a potent angiogenicfactor. Material and Method: To evaluate mast cells count using 1%standard Toluidine Blue stain,15 tissue sample of normal epithelial mucosa, 10 samples of each of low to high grades of dysplasia along with 10 samples each of low to high grades OSCC were taken for the study. Followed by comparison of mast cell count in these following groups.Result: On comparing the mast cell counts in different grades of epithelial dysplasia with normal oral mucosa we found that there is increase in number of mast cells from mild to severe dysplasia on the contrary the mast cells count in well differentiated OSCC was higher while comparing to the moderately differentiated OSCC and poorly differentiated OSCC. When comparison was analysed between low to high grades of dysplasia and OSCC it was demonstrated that more number of mast cells were found in epithelial dysplasia as compare to OSCC.Conclusion: It was concluded that mast cells can be used as an indicator to evaluate increased angiogenesis which is corelated with the increased progression of potentially malignant disorder into malignant lesions.